The roles of lipid mediators in type I hypersensitivity - Tatsuro Nakamura (Elsevier, 2021)
Type I hypersensitivity is an immediate immune reaction that involves IgE-mediated activation of mast cells. Activated mast cells release chemical mediators, such as histamine and lipid mediators, which cause allergic reactions. Recent developments in detection devices have revealed that mast cells simultaneously release a wide variety of lipid mediators. Mounting evidence has revealed that mast cell-derived mediators exert both pro- and anti-inflammatory functions and positively and negatively regulate the development of allergic inflammation. This review presents the roles of major lipid mediators released from mast cells. Author believes this review will be helpful for a better understanding of the pathogenesis of allergic diseases and provide a new strategy for the diagnosis and treatment of allergic reactions.